OVERVIEW OF THE IMPLEMENTATION OF HEALTH PROTOCOLS IN COMMUNITY ACTIVITIES IN PULAU PANDAN VILLAGE AND KARANG PANDAN VILLAGE, KERINCI REGENCY IN 2022 - Zulfamitra, Feby; Subandi, Andi; Mekeama, Luri (Jurnal Pinang Masak, 2023)
The increase in Covid-19 cases from time to time is not only caused by the rapid spread of the Covid-19 virus but also influenced by community activities. Based on observations made by researchers in the community in Pulau Pandan Village and Karang Pandan Village, Kerinci Regency, it was found that many people carried out activities outside the home such as kenduri, community meetings, schools and other activities, even though at that time PPKM Level 3 was being implemented in Jambi Province. These restrictions were not adhered to by the people of Pulau Pandan Village and Karang Pandan Village. The dense community activities were not provided with facilities to prevent the transmission of Covid-19, no place to wash hands, masks, hand sanitizers were provided, no distance was maintained and there were no restrictions on activity time. This type of research uses a descriptive observational design with a cross-sectional research design. This research was conducted in Pulau Pandan Village and Karang Pandan Village, Kerinci Regency. The population of the entire community in Pulau Pandan Village and Karang Pandan Village with a sample size of 318 respondents. Sampling used the Cluster Random Sampling method. Data analysis used univariate frequency distribution analysis. The implementation of public health protocols in Pulau Pandan village during village meetings was categorized as not complying with 36 people (55.5%), during thanksgiving events it was categorized as not complying with 43 people (78.1%) and when in the school environment it was categorized as not complying with 33 people (60%). The implementation of health protocols in Karang Pandan village during village meetings was categorized as not complying with 27 people (53%), during thanksgiving events it was categorized as not complying with 38 people (74.5%) and when in the school environment it was categorized as not complying with 22 people (40%). The description of the implementation of health protocols in community activities during the Covid-19 pandemic in Pulau Pandan Village and Karang Pandan Village, Kerinci Regency was categorized as not complying. It is hoped that the community can increase awareness and be able to implement health protocols in carrying out every activity in the crowd. Keywords: Covid-19, Health Protocols. can increase awareness and be able to implement health protocols in carrying out every activity in a crowd of people.